Synthesis, Structural and Spectroscopic Characterization of [MnCl4](L1.H)2 Complex Derived from Manganese(II) Chloride and Novocaine Hydrochloride - F.Q.Matmurodova; A.K.Masharipova; D.S.Xaitboyev (Genius Journals, 2025)
This study reports the synthesis and characterization of a manganese(II) complex with protonated novocaine. The complex was prepared by reacting MnCl₂ (0.005 mol) and novocaine hydrochloride (0.01 mol) in aqueous solution under magnetic stirring at 800 rpm for 1.5 hours, followed by slow evaporation for 21 days, yielding crystalline [MnCl4](L1·H)2. X-ray diffraction revealed a monoclinic system (I2/a) with Mn²⁺ coordinated by four chloride ions in a distorted tetrahedral geometry. IR spectroscopy confirmed N–H, C–H, C=O, and Mn–Cl vibrational modes, while UV-Vis analysis showed d–d transitions (λ_max = 508 nm) and ligand-centered π→π*, n→π* absorptions. SEMEDS mapping validated elemental composition and coordination effects on ligand microstructure. Thermal analysis showed two main decomposition stages between 183– 215 °C and 245–424 °C, with mass loss indicating improved thermal stability. XRD patterns and diffractograms confirmed the individuality of the complex compared to the free ligand. The reproducible spectroscopic, crystallographic, and morphological results suggest the complex's potential for further studies in coordination chemistry and material science.
Keywords: Manganese; complex; Novocaine hydrochloride; Infrared spectroscopy